(3GdGNHGQ GdGPGYjI h GdJdaRjhfjI (B:s (3GdJMQjQ(B...(3G dJUhjQ(B... (3GdYQV(B... (3GdJbOje (B/s - (3NVhQ, COjHs; (3EjQajfZ aGfZs ((3ShQjG(B;(3OeTb (B:s (3GdecJHI GdGYdGejI ,s, 2009)
(3jbOe gPG GdcJGH QDjI GeQjcjI deYGdLI GdLhGfH GdMQajI h GdafjI aj YedjI GdJZWjI GdGNHGQjI GdGPGYjI h GdJdahjhfjI (B. (3eG eYGjjQ GfJbGA GdGNHGQ aj GdGPGYI h GdJdaRjhf ?heG GdGSS GdYdejI h GdHafjI ddJZWjI GdGNHGQjI hab NUhUjI GddZI GdGPGYjIh GdJdaRjhfjI ? h eG GdGSGdjH GdMOjKI aj JMQjQ GdGNHGQ h GdJbGQjQ GdGNHGQjI GdGPYjI h GdJdaRjhfjI (B, (3h eG WQb YQVgG h JbOjegG ? eG MbjbKI GdYdGbI Hjf GdcdeI h GdUhQI aj GdJZWjI GdGNHGQjI GdJdaRjhfjI ? cja jLH JUhjQ GdNHQ GdJdaRjhfj (B, (3h JMQjQg h cJGHI eGOJg GdcdGejI h JbOjeg HdWQb JVef JMbjb GdMOI Hjf GdcdeI h GdUhQI ? jMGhd gPG GdcJGH JbOje GLGHGJ eYebI Yf gPg GdGSFdI JLeY Hjf GdLhGfH GdfXQjI h GdYdejI aj GdJZWjI GdGNHGQjI (B.s
(3H(B.(3d (B: (3-6)s
Keywords: (3GdCNHGQ s; (3GdUMGaI s; (3GdEPGYIs; (3GdJdaRjhf s